2021
DOI: 10.3389/fonc.2020.602555
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Immune-Related Gene Signature for Prognosis in Melanoma

Abstract: Melanoma remains a potentially deadly malignant tumor. The incidence of melanoma continues to rise. Immunotherapy has become a new treatment method and is widely used in a variety of tumors. Original melanoma data were downloaded from TCGA. ssGSEA was performed to classify them. GSVA software and the "hclust" package were used to analyze the data. The ESTIMATE algorithm screened DEGs. The edgeR package and Venn diagram identified valid immune-related genes. Univariate, LASSO and multivariate analyses were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
(54 reference statements)
2
16
0
Order By: Relevance
“…We also identified a subset of THYM patients with overall low V-gene usage, although we could not find significant associations between this subset of patients and any clinical variables. In our hierarchical clustering analysis, we identified clusters of V-genes in each chain that had higher overall usage across the tumor types which were largely consistent with previous studies (56,57). For the IGL Vgene analysis, we found that the IGLV2-14 V-gene formed its own cluster and seems to have relatively high usage across many tumor samples.…”
Section: Discussionsupporting
confidence: 86%
“…We also identified a subset of THYM patients with overall low V-gene usage, although we could not find significant associations between this subset of patients and any clinical variables. In our hierarchical clustering analysis, we identified clusters of V-genes in each chain that had higher overall usage across the tumor types which were largely consistent with previous studies (56,57). For the IGL Vgene analysis, we found that the IGLV2-14 V-gene formed its own cluster and seems to have relatively high usage across many tumor samples.…”
Section: Discussionsupporting
confidence: 86%
“…Just recently, survival prognosis in melanoma was correlated with immune-related gene signatures (70)(71)(72). Of note, Danaher et al (73) found that TIS was also highly statistically significantly prognostic in TCGA-SKCM, limiting its predictive value in melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we grouped all SKCM samples into high and low expression groups according to the median expression of the novel prognostic gene and used the ssGSEA package 27 to perform enrichment analysis of the Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, and MsigDB dataset (msigdb.v7.0.entrez.gmt). The ggplot2 package (version 3.3.3) was used for visualization.…”
Section: Methodsmentioning
confidence: 99%